Bioinspired Multifunctional Ceramic Platelet‐Reinforced Piezoelectric Polymer Composite2 . Issue 2 (17th October 2016) - Xu, Zhe; Bykova, Julia; Baniasadi, Mahmoud; Moreno, Salvador; Zhou, Zhong; Das, Nandita; Bandi, Sasaank; Xi, Yang; Qian, Dong; Baughman, Ray H.; Minary‐Jolandan, Majid
Abstract : Hybrid materials of inorganic–organic phases in which each phase provides different functionality are attractive candidates for achieving multifunctionality. Using a layer‐by‐layer approach, we fabricated sheets of piezoelectric polymer P(VDF‐TrFE) reinforced by aligned sub‐micron thick sapphire platelets. The films were transparent and piezoelectric, exhibited ductility up to ≈330%, and tensile toughness of up to 26 J g –1 . We investigated the effect of thermal annealing on the crystallinity of the polymer phase and its effect on the mechanical and piezoelectric properties of the films. Thermal annealing resulted in improvement of the elastic modulus and piezoelectric properties of the films. in situ SEM tensile experiments were conducted for observation of the deformation mechanism of the films. Abstract : Bioinspired multifunctional composite of single crystal ceramic platelets and piezoelectric polymer prepared by layer‐by‐layer approach is described. The composite is transparent, is piezoelectric, and shows large ductility. Effect of the annealing process on the morphology of the polymer phase and on the mechanical properties of the composite is also investigated.